Особливості правової моделі ханафітського мазгабу - Ісмагілов, С. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2010)
Статья Исмагилова С.В. «Особенности правовой модели
ханафитского мазхаба» исследует возникновение и развитие ханафитского
мазхаба – правовой школы имама Абу Ханифы. В работе автор исследует
источники фикха, феномен возникновения мазхабов и особенности правовой
модели ханафитского мазхаба. В статье подчеркивается, что мазхаб ханафитов
явился результатом научно-правовой деятельносты не только самого Абу
Ханифы, но также и его учеников.
Ключевые слова: ханафитский мазхаб, мусульманское право, иджтихад. The article by Ismagilov S.V. "Features of the jural model of the Hanafi
school of thought" investigates the origin and development of the Hanafi school of
thought - the juridical school of Imam Abu Hanifa. In this paper, the author analyses
the sources of fiqh, the phenomenon of emergence of schools of thought and
peculiarities of the juridical model of the Hanafi school of thought. The paper stresses
that Madh'hab Hanafi is a product of scientific and jural activities not only of Abu
Hanifa, but his disciples also.
Key-words: juridical school of Abu Hanifa, Moslem jury, idgtikhad.